Wrongful Damage to Property in Roman Law : British perspectives - Plessis, Paul J. du (Edinburgh University Press, 2017)
This volume investigates the peculiarly British fixation with the the lex Aquilia, a Roman statute enacted c.287/286 BCE to reform the Roman law on wrongful damage to property, against the backdrop larger themes such as the development of delict/tort in Britain and the rise of comparative law.